ANALYSIS OF INFLUENCE OF THE VISCO-ELASTIC CHARACTERISTIC ON ASPHALT PEN 60/70 WITH STYRENE BUTADIANE STYRENE (SBS) AS ADDITION IN MECHANISTIC RHEOLOGY FIELD - Manalu, Ramot
Adding plastic waste (polymer) into asphalt is one of many ways to improve the quality of asphalt. Polymer (SBS) has opportunity to be used as a binder in asphalt pavement, that way the asphalt will be more elastic and durable with mixing Styrene Butadiane Styrene (SBS) into Asphalt Pen 60/70. According to basic rheology testing on asphalt pen 60/70 and Styrene Butadiane Styrene (SBS), SBS addition are decreasing the penetration value. On the contrary, softening point value and elastic recovery value are increasing and there’s no effect on ductility value. However, viscosity value are increasing the mixing temperature and compacting temperature in addition of SBS. According to mechanistic rheology testing with DSR tool (time sweep), the result shows that SBS addition increase the Complex Shear Modulus (G*) and Elastic Modulus (E*) value. Meanwhile, it decrease the Phase Angle (?) and Strain (?) value. Moreover, the mechanistic rheology testing (temperature sweep) shows that SBS addition decrease the Complex Shear Modulus (G*) value and increase the Phase Angle (?) value. Other than that, it shows that higher SBS content will increase the capability of pavement to resist the failures such as permanent deformation and fatigue cracking.